Mechanisms of Cadmium-Induced Proximal Tubule Injury: New Insights with Implications for Biomonitoring and Therapeutic Interventions - Prozialeck, Walter C. (The American Society for Pharmacology and Experimental Therapeutics, 2012)
Cadmium is an important industrial agent and environmental pollutant that is a major cause of kidney disease. With chronic exposure, cadmium accumulates in the epithelial cells of the proximal tubule, resulting in a generalized reabsorptive dysfunction characterized by polyuria and low-molecular-weight proteinuria. The traditional view has been that as cadmium accumulates in proximal tubule cells, it produces a variety of relatively nonspecific toxic effects that result in the death of renal epithelial cells through necrotic or apoptotic mechanisms. However, a growing volume of evidence suggests that rather than merely being a consequence of cell death, the early stages of cadmium-induced proximal tubule injury may involve much more specific changes in cell-cell adhesion, cellular signaling pathways, and autophagic responses that occur well before the onset of necrosis or apoptosis. In this commentary, we summarize these recent findings, and we offer our own perspectives as to how they relate to the toxic actions of cadmium in the kidney. In addition, we highlight recent findings, suggesting that it may be possible to detect the early stages of cadmium toxicity through the use of improved biomarkers. Finally, some of the therapeutic implications of these findings will be considered. Because cadmium is, in many respects, a model cumulative nephrotoxicant, these insights may have broader implications regarding the general mechanisms through which a variety of drugs and toxic chemicals damage the kidney.